The role of trust and religious commitment in Islamic medical tourism - Iranmanesh, Mohammad; Moghavvemi, Sedigheh; Zailani, Suhaiza; Hyun, Sunghyup Sean (Taylor & Francis, 2018)
This study has examined the effect of trust and religiosity on Islamic medical tourists’ attitudes, and consequently, satisfaction by considering age, gender, and education as moderators. A survey was undertaken of 227 Muslim medical tourists who had been treated in Islamic hospitals in Iran, and the data were analysed using partial least squares techniques. The results showed that although trust has a significant effect on Muslim medical tourists’ attitudes, religiosity has no significant effect. The relationship between attitude and satisfaction towards the Islamic medical treatment practised by the healthcare providers is also supported. Gender and education moderate the relationship between religiosity and attitude. In addition, education moderates the relationship between trust and attitude. The results of this research can provide useful insight into the needs of Muslim medical tourists, which would be useful for Islamic hospitals to provide higher quality healthcare services.